(untitled) (Journal of actual problems of jurisprudence, 2018)
In article it is considered a food safety., including country animal husbandry.To analyse measures accepted by Kazakhstan, state of problem on this day and in tomorrow, public opinion in the field of food safety that becomes world problem. It is Advantageous to use the natural state Kazakh earth. it is Advantageous to use the natural state Kazakh earth. That agricultural to the products 40% made is GDP, fully to provide people by quality food, to use everything climate to possibility. Keywords: food safety, animal husbandry, kosyachny economy of the hinny.